The Optimization of Electrocoagulation Process Efficiency in the Removal of Amoxicillin Antibiotic and COD from Aqueous Solutions and Hospital Wastewater under Optimal Conditions: A Case Study of Alimoradian Hospital, Nahavand - Gholamreza Karim Mehrabankhahi; Mostafa Leili; Reza Shokooni; Alireza Rahmani; Ghasem Azarian; Nasrin Shirmohammadi Khorram; Mahmood Razavi (مجله علمی دانشگاه علوم پزشکی کردستان, 2023)
Background and Aim: Amoxicillin antibiotic is one of the antibiotics which is used in medicine and veterinary medicine to treat bacterial infectious diseases. In this study, a special electrochemical cell design was used as it could integrate the process units and the operation units to reduce COD and amoxicillin antibiotic residues from the wastewater of Alimoradian Hospital. Also, to optimize the operational parameters, the central composite design of response surface methodology (RSM) was used. Materials and Methods: This experimental study was conducted in two parts. In the first stage, synthetic wastewater was prepared from Amoxicillin antibiotics to investigate the effect of various parameters such as reaction time, initial antibiotic concentration, current density, and pH on the efficiency of the method. In the second stage, the efficiency of the method in removing the antibiotic and reducing COD from the actual wastewater of Alimoradian hospital was evaluated. Results: Using the RSM, the optimal conditions of the laboratory findings were determined as follows: reaction time = 30 min, pH = 7.5, current density = 2.31 mA/cm2, and initial concentration of amoxicillin = 54.66 mg/L. Under these conditions, the removal amount of amoxicillin was 90.56%. The results also showed that under optimal conditions, the removal rate of COD and TOC from synthetic wastewater is 65.5% and 44.5%, respectively, and in the effluent of Alimoradian hospital is 47.7% and 38%, respectively. The reason for this difference is probably due to the presence of some resistant compounds in the real wastewater. Conclusion: This experimental study showed that the combined electrocoagulation process can be a more effective method in removing the amoxicillin antibiotic and COD from aqueous solutions and hospital wastewater.